The value of cytologic diagnostics in fast intraoperative diagnosis of mediastinal lymphadenopathy and pulmonary and mediastinal tumors - Tatomirović Željka; Bokun Radojka; Stoiljković Bratislav; Stepić Vlado (Vojnosanitetski Pregled)
Extemporary (EXT) analysis is unavoidable in establishing the tumor diagnosis, operability and the extent of the operation. Alternative approach is cytologic analysis which, because of its simple methodology, provides results even faster. In this paper, the results of cytologic imprints (CI) and EXT finding were compared with definite histopathologic diagnosis (HDP) to determine the value of both methods. A total of 109 samples obtained during 55 thoracotomies were analyzed. Eighty eight specimens were analyzed simultaneously by CI Method and in frozen sections. Twenty one sample was analyzed only by cytologic methods and the results of standard CI were compared with definite HDP. After being processed for EXT diagnosis, intraoperative specimens were imprinted on glass slides, air-dried and stained by May-Grünwald-Giemsa Method. In cytologic analysis there were no false negative results, but there were 7 false positives. The overall diagnostic accuracy was 93.6%, sensitivity and negative predictive value was 100%, specificity was 91.1% and positive predictive value was 81.8%. Diagnostic accuracy of frozen sections was 98.8% also without false negatives and with one false positive finding with sensitivity and negative predictive value of 100%, specificity of 98.4% and positive predictive value of 95%. These results corresponded to the results of other studies and confirmed the efficacy of CI method, which could be used either simultaneously with EXT diagnosis as a complementary or as an alternative method in the hospitals where EXT analysis is not used. However, imprint cytology demands an experienced cytologist and could be used only in hospitals with well organized cytologic service.